Analysis Potential of Solar and Wind as Power Plant in Bontang Kuala Using Software Homer: Analisis Potensi Energi Matahari dan Angin Sebagai Pembangkit Listrik di Bontang Kuala Menggunakan Software Homer - Sakti, Bima; Burhandenny, Aji Ery; Utomo, Restu Mukti; Nugroho, Happy; Wirawan, Adi Pandu (Muhammadiyah University, Sidoarjo, 2024)
The increasing need for electrical energy is becoming a problem due to limited fossil energy, so it is necearry to know locations that have the potential to generate electricity from renewable energy. This study simulates and analyzes the potential of solar and wind energy in Bontang Kuala as a power plant using Homer software. Load planning uses a peak load of 38,44 kW and usage of 471,56 kWh/day from the results of a survei conducted at one of the RTs in Bontang Kuala. The simulation produces three optimal configurations of three types of generators, namely Solar Cell, Hybrid Power Plant and Wind Power Plant. The most optimal configuration is the Solar Cell system with the smallest NPC value of Rp3,6 B and this system has a solar panel capacity of 142 kW, a battery capacity of 461 kWh and an inverter capacity of 50 kW.